SEAMEO basic education standards (SEA-Bes) : (SEAMEO RECSAM, 2017)
SEAMEO RECSAM with its mandate to promote science and mathematics in the Southeast Asian region, led one of the 12 initiatives known as SEAMEO Basic Education Standards (SEA-BES) and Student Networking, which later became two separate projects. The SEA-BES project came into life in November 2014 through a regional consultative meeting back to back with the Southeast Asia Primary Learning Metrics (SEA-PLM) project with funding from UNICEF East Asia Pacific Regional Office (UNICEF EAPRO).